A GODDESS DEFIED - Chacko, Arun M. (SCHOOL SCIENCE, 2013)
Late in May 1975, at the sleepy little eastern border town of Karimganj, Indian smallpox field workers zeroed in on the railway station and successfully isolated a victim of the disease —Saiban Bibi, aged 30, a woman migrant from Bangladesh. That was the last time any of the several thousand people employed by India’s Smallpox Eradication Programme had occasion to use their skills. It had been far from smooth sailing, and at the outset there was a critical shortage of manpower. Mr. L.R. Tiwari, a former vaccination inspector who spent 20 years combating smallpox told me: “Before 1960, Delhi with 2.5 million people had just one vaccination superintendent and 35 vaccinators (and the capital has always been more fortunate than the rest of the country). When the smallpox pilot project was started in 1960, staff strength was raised to 37 inspectors and 176 vaccinators. This permitted a door-to-door survey of the entire population and every individual got his or her primary vaccination”.